Germline pathogenic variants in PALB2 and other cancer-predisposing genes in families with hereditary diffuse gastric cancer without CDH1 mutation: a whole-exome sequencing study. (July 2018) - Fewings, Eleanor; Larionov, Alexey; Redman, James; Goldgraben, Mae A; Scarth, James; Richardson, Susan; Brewer, Carole; Davidson, Rosemarie; Ellis, Ian; Evans, D Gareth; Halliday, Dorothy; Izatt, Louise; et al.
Summary: Background: Germline pathogenic variants in the E-cadherin gene ( CDH1 ) are strongly associated with the development of hereditary diffuse gastric cancer. There is a paucity of data to guide risk assessment and management of families with hereditary diffuse gastric cancer that do not carry a CDH1 pathogenic variant, making it difficult to make informed decisions about surveillance and risk-reducing surgery. We aimed to identify new candidate genes associated with predisposition to hereditary diffuse gastric cancer in affected families without pathogenic CDH1 variants. Methods: We did whole-exome sequencing on DNA extracted from the blood of 39 individuals (28 individuals diagnosed with hereditary diffuse gastric cancer and 11 unaffected first-degree relatives) in 22 families without pathogenic CDH1 variants. Genes with loss-of-function variants were prioritised using gene-interaction analysis to identify clusters of genes that could be involved in predisposition to hereditary diffuse gastric cancer. Findings: Protein-affecting germline variants were identified in probands from six families with hereditary diffuse gastric cancer; variants were found in genes known to predispose to cancer and in lesser-studied DNA repair genes. A frameshift deletion in PALB2 was found in one member of a family with a history of gastric and breast cancer. Two different MSH2 variants were identified in two unrelated affected individuals, including one frameshift insertion and one previously described start-codon loss. One family had a unique combination of variants in the DNA repair genes ATR and NBN . Two variants in the DNA repair gene RECQL5 were identified in two unrelated families: one missense variant and a splice-acceptor variant. Interpretation: The results of this study suggest a role for the known cancer predisposition gene PALB2 in families with hereditary diffuse gastric cancer and no detected pathogenic CDH1 variants. We also identified new candidate genes associated with disease risk in these families. Funding: UK Medical Research Council (Sackler programme), European Research Council under the European Union's Seventh Framework Programme (2007–13), National Institute for Health Research Cambridge Biomedical Research Centre, Experimental Cancer Medicine Centres, and Cancer Research UK.